Efficacy and safety of nucleoside antiviral drugs for treatment of recurrent herpes labialis: a systematic review and meta‐analysis. (25th January 2017) - Chen, Fangman; Xu, Hao; Liu, Jinli; Cui, Yuan; Luo, Xiaobo; Zhou, Yu; Chen, Qianming; Jiang, Lu
Abstract : Objectives: To evaluate the effectiveness and safety of nucleoside antiviral drugs for the treatment of recurrent herpes labialis. Methods: Randomized controlled trials that examined the effectiveness and/or safety of nucleoside antiviral drugs for recurrent herpes labialis were identified via a literature search. The parameters used to measure efficacy were time to healing of classic and all lesions, time to resolution of pain, and percentage of aborted lesions. Safety was assessed by evaluating the adverse events reported during treatment. Subgroup analyses based on the mode of application (topical/systemic) and type of nucleoside antiviral drugs were performed, as were sensitivity analyses of studies with a low risk of bias. Results: Our analysis included 16 publications reporting 25 randomized controlled trials (8453 patients). Nucleoside antiviral drugs decreased the time to healing of all lesions (mean difference: −0.74 days; 95% confidence interval: −0.86, −0.62), especially classic lesions (mean difference: −1.09 days; 95% confidence interval: −1.27, −0.92). They also reduced the time to resolution of pain (mean difference: −0.38 days; 95% confidence interval: −0.58, −0.18) and increased the percentage of aborted lesions (rate ratio: 1.15; 95% confidence interval: 1.07, 1.23). Valaciclovir more effectively reduced the time to healing of all lesions and the time to resolution of pain than did aciclovir. Both nucleoside antiviral drugs increased the percentage of aborted lesions, whereas penciclovir and famciclovir did not. Conclusions: Nucleoside antiviral drugs are safe and beneficial for the treatment of recurrent herpes labialis; both systemic and topical formulations are recommended. Valaciclovir is more effective than aciclovir, especially in reducing the time to healing of lesions.